New crabs from hydrothermal vents of the Kermadec Ridge submarine volcanoes, New Zealand: Gandalfus gen. nov. (Bythograeidae) and Xenograpsus (Varunidae) (Decapoda: Brachyura) - Mclay, Colin (Zootaxa, 2007)
Gandalfus puia gen. et sp. nov. (Bythograeidae) is reported from submarine volcanoes near the Kermadec Islands. The genus Austinograea is revised with the result that A. yunohana Takeda, Hashimoto & Ohta, 2000 is transferred to the new genus. Both of these species occur in relatively shallow waters (240–1650 m) compared to other bythograeids. A sister group hypothesis of the modern genera, Allograea + (Segonzacia + (Cyanagraea + (Bythograea + (Gandalfus + Austinograea)))) is presented to provide an interpretation of variation in eye regression and male gonopods; Austinograea and Gandalfus are the most derived genera. The pattern of eye regression with depth is discussed. A varunid, Xenograpsus ngatama sp. nov., also collected from these volcanoes, is the first record of this genus from the southern hemisphere. Keys to all known species of the family Bythograeidae (13 species 6 genera) and to the genus Xenograpsus (3 species) are presented.